(untitled) (Bangladesh Journal of Medical Education, 2026)
Background: Dental practitioners were among the most vulnerable professionals throughout the COVID-19 pandemic due to their exposure to aerosols and close patient contact. This study assessed the physical and psychological health challenges faced by dental practitioners in Chattogram City. Methods: This cross-sectional study was conducted amongst 96 dental practitioners of Chattogram city, from May 2023 to April 2024. Data were collected using a structured, pretested online questionnaire covering demographic details, physical symptoms, psychological impacts, and infection-control practices in dental clinics. Descriptive statistics and Chi-square/ Fisher’s exact tests were applied as appropriate (p<0.05 considered statistically significant). Results: The majority of participants were male (57.3%), and within the 31–40 age group (46.8%). Breathing difficulties (70.8%), fatigue and body ache (59.4%), and headaches (57.3%) were the most common physical complaints. Musculoskeletal pain and dermatological problems related to prolonged PPE use were also prevalent. Psychologically, 81.2% reported anxiety regarding infection transmission to family, and 65.6% feared treating patients in proximity. Notably, 76.0% of practitioners reported COVID-19 infection (self or family). Female practitioners were more likely to report headaches and musculoskeletal pain (p<0.05), while dentists over 40 years reported significantly greater anxiety affecting treatment decision-making (p=0.035). No significant association was noticed between clinic air-control measures and infection status. Conclusion: Dental practitioners in Chattogram experienced substantial physical discomfort and psychological stress throughout the COVID-19 pandemic, with significant gender- and age-related differences. These conclusions highlight the necessity for specific occupational health support and preparedness strategies for future pandemics. BJME: Vol.-17, Issue-01, January, 2026: 69-79